Identifikasi Spesies Burung Di Hutan Rawa Bento Kawasan Taman Nasional Kerinci Seblat: Identification of Bird Species in Rawa Bento Forest Kerinci Seblat National Park Area - Wulan, Cory; Aulia, Muhammad Fadli Putra; Khabibi, Jauhar (Jurnal Silva Tropika, 2023)
ABSTRACT Rawa Bento is a swamp forest located in Kerinci Seblat National Park which is included in the jungle zone. Rawa Bento is the highest swamp in Sumatra, at an altitude of 1375 meters above sea level. This swamp area has an area of approximately 1000 ha and also has three swamp ecosystems namely peat swamp grass, dwarf swamp forest, and small swamp lakes. Rawa Bento is a natural tourism area that has a natural ecosystem and has a beautiful and diverse natural community, one of which is bird species. Birds are a good indicator of environmental health and biodiversity value. This study aims to identify bird species in the Rawa Bento swamp forest of Kerinci Seblat National Park. The research was conducted for two months starting from December 2022 to January 2023. The research was conducted using the point count method. Determination for the observation path with purposive sampling. The results of the study identified as many as 10 species of birds from 7 families. The endemic bird species encountered are cream-striped bulbul (Hemixos leucogrammicus) and the sumatran whistling-thrush (Myophonus castaneus). The bird species identified were mostly found in the dwarf swamp forest ecosystem. Keywords: Bird, ecosystem, Rawa Bento, swamp forest ABSTRAK Hutan rawa bento merupakan hutan rawa yang terletak di Taman Nasional Kerinci Seblat yang termasuk ke dalam zona rimba. Rawa Bento termasuk rawa tertinggi yang berada di Sumatera yaitu berada di ketinggian 1375 mdpl. Kawasan rawa ini mempunyai luas kurang lebih 1000 ha dan juga memiliki tiga ekosistem rawa yakni rumput rawa gambut, hutan rawa kerdil, serta danau rawa kecil. Rawa Bento merupakan kawasan wisata alam yang memiliki ekosistem yang masih alami dan mempunyai komunitas alam yang indah dan beranekaragam, salah satunya spesies burung. Burung merupakan salah satu indikator yang baik bagi kesehatan lingkungan dan juga nilai keanekaragaman hayati. Penelitian ini bertujuan untuk mengidentifikasi spesies burung di hutan rawa bento kawasan taman nasional kerinci seblat. Penelitian dilakukan selama dua bulan mulai dari bulan desember 2022 hingga januari 2023. Penelitian dilakukan dengan menggunakan metode point count. Penentuan untuk jalur pengamatan dengan purposive sampling. Hasil penelitian teridentifikasi sebanyak 10 spesies burung dari 7 famili. Spesies burung endemik yang dijumpai yaitu burung cucak kerinci (Hemixos leucogrammicus) dan ciung batu sumatera (Myophonus castaneus). Spesies burung yang teridentifikasi lebih banyak ditemukan pada ekosistem hutan rawa kerdil. Katakunci: Burung, ekosistem hutan rawa, Rawa Bento